Analisis Kesiapan dan Strategi Monitoring Evaluasi Program Pengembangan Perkuliahan Gelombang dan Optik Berbasis Game - Saprudin Saprudin (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2018)
This study is a survey focused on describing how the level of readiness of pre-service physics teachers and descriptions the elements of strategy to monitor and evaluate the program of wave and optic course based on game. The survey involved 41 students (9 M, 32 F) who joined waves and optics courses in physics education program at one of university in Ternate, Indonesia. Data were collected through questionnaire and analyzed by using descriptive technique. The results show that pre-service physics teachers in the population can be categorized into good in readiness in the implementation the program of wave and optic based on game. The readiness was supported by several indicators which are readiness related to game experience, game play frequency, game play device, game ownership support, device ownership and internet access capability, students' perception about the use of games in physics learning, the ability to design game, the need analysis for training to design educational games. The model used for program monitoring and evaluation was CIPP model (Context, Input, Process and Product).